2014
DOI: 10.1111/zoj.12124
|View full text |Cite
|
Sign up to set email alerts
|

Vicariant versus dispersal processes in the settlement ofPseudamnicola(Caenogastropoda, Hydrobiidae) in the Mediterranean Balearic Islands

Abstract: The genus Pseudamnicola comprises a group of tiny springsnails inhabiting several continental and insular regions of the Mediterranean basin. Given the limited dispersal capabilities of these animals, it is difficult to explain the wide distribution range of the genus and, more specifically, its presence in isolated habitats, such as on islands. Thus, to investigate the process(es) that may explain these distribution patterns, we morphologically re-described and genetically analysed the six Pseudamnicola (Pseu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 73 publications
0
30
0
Order By: Relevance
“…However, our findings indicated that peninsular ecoregions, which are supposed to be geographically isolated and species poor, are actually as diverse as nonpeninsular ecoregions. The peninsula effect may have been counteracted by past colonisation of the southern peninsulas during glacial episodes (as mentioned above) and long‐distance dispersal by birds, which has also been suggested to play an important role in the geographic distribution of certain hydrobiid species (Delicado, Machordom, & Ramos, ; Haase et al., ; Szarowska, Osikowski, Hofman, & Falniowski, ). The importance of historical factors is also reflected in the variation of species richness found among biogeographic realms (Figure ).…”
Section: Discussionmentioning
confidence: 99%
“…However, our findings indicated that peninsular ecoregions, which are supposed to be geographically isolated and species poor, are actually as diverse as nonpeninsular ecoregions. The peninsula effect may have been counteracted by past colonisation of the southern peninsulas during glacial episodes (as mentioned above) and long‐distance dispersal by birds, which has also been suggested to play an important role in the geographic distribution of certain hydrobiid species (Delicado, Machordom, & Ramos, ; Haase et al., ; Szarowska, Osikowski, Hofman, & Falniowski, ). The importance of historical factors is also reflected in the variation of species richness found among biogeographic realms (Figure ).…”
Section: Discussionmentioning
confidence: 99%
“…Notwithstanding, this would need confirmation through more comprehensive sampling of the area and examining other potential new representatives of this lineage. As more shared synapomorphies with the pyrgulinid group were detected (such as a tapered penis, zero to two seminal receptacles, zero to three pairs of basal cusps in the central radular tooth and spiral keels on the shell, see Radoman 1955Radoman , 1983 than with Pseudamnicola (diagnosed by, one elongate seminal receptacle, one pair of basal cusps in the central radular tooth, triangular penis with folds and simple shells slightly longer than wide, of which the latter two are not present in Pyrgulinae, see Boeters 1988;Szarowska et al 2009;Delicado et al 2014), we tentatively consider these taxa as belonging to the subfamily Pyrgulinae.…”
Section: Discussionmentioning
confidence: 99%
“…Pseudamnicola species, like most hydrobiids, are characterized by a minute, unsculpted shell and simple penis, such that only comprehensive studies including the description of several anatomical structures and molecular data have been able to distinguish among congeners (Hershler & Ponder 1998;Wilke et al 2001;Arconada & Ramos 2003;Strong et al 2008). Morphological and molecular data may offer varying resolution in cases of cryptic species (Wilke et al 2002;Liu et al 2003; or when high morphological disparity exists among close related taxa (Wilke et al 2007;Delicado et al 2014). Thus, unraveling the systematics of the hydrobiids family calls for an integrative approach.…”
Section: Introductionmentioning
confidence: 99%
“…The second Miocene land connection is considered by many authors to be one of the main events driving local diversification in the Mediterranean, and this event has been dated to the Messinian salinity crisis (MSC; 5.96–5.33 Ma), when closure of the Strait of Gibraltar led to desiccation of the Mediterranean Basin (Hsü et al ., ; Krijgsman et al ., ). During this dry period, a colonization event from the mainland to the Balearic Islands took place (Fromhage et al ., ; Lalueza‐Fox et al ., ; Delicado et al ., ). The refilling of the Mediterranean Basin following the MSC restored the isolation of the Balearic Islands.…”
Section: Introductionmentioning
confidence: 97%